Universal prenatal screening: a initiative from Guanajuato, Mexico to improve equity in perinatal healthcare - Bermudez Rojas, Ma de la Luz; Medina Jimenez, Virginia; Manzanares Cuadros, Javier Ivan; Diaz Martínez, Daniel Alberto; Padilla Raygoza, Nicolas; Lara Lona, Elia (Frontiers in Medicine, 2023)
The prenatal approach from a preventive perspective is necessary to reduce perinatal complications. A perinatal care model with a holistic and horizontal approach is required. Mexico is currently considered an emerging market economy with inequality and an economic gap that impacts the accessibility and distribution of healthcare services. Guanajuato is one of the 32 states of Mexico and represents 1.6% of the country´s surface. Strategies during the prenatal approach allow prediction, diagnosis, and anticipation of the principal causes of morbidity and mortality. Combining data from maternal characteristics and history with findings of biophysical and biochemical tests at 11 to 13 weeks of gestation can define the patient-specific risk for a large spectrum of complications that include miscarriage and fetal death, preterm delivery, preeclampsia, congenital disorders, and fetal growth abnormalities. We aim to describe the care model designed and implemented in the State Center for Timely Prenatal Screening of the Maternal and Child Hospital of Leon, Guanajuato, Mexico. Previous research showed there is a lack of information for low and middle-income countries regarding how to integrate prenatal screening strategies in the absence of resources to perform cell-free fetal DNA or biochemical serum markers in countries with emergent economies. This care model is carried out through horizontal processes where the screening is provided by trained and certified general practitioners who identify the population at risk in a timely manner for specialized care, and could help guide other Mexican states, and other countries with emergent economies with limited financial, professional, and infrastructural resources to improve prenatal care with a sense of equity, equality, and social inclusion as well as the timely evaluation of specialized perinatal care of high-risk patients.